PERKEMBANGAN PERADABAN DI KAWASAN SITUS TAMBLINGAN - Anak Agung Gde Bagus (Forum Arkeologi, 2013)
Research on civilization of Tamblingan site is a part of the research on Development of Tamblingan area for Tourist Destination which was done by Balai Arkeologi Denpasar in 2012. The research of The Development of Civilization at Tamblingan Site Area aims to know the history of the residential and social culture that flourished in the region Tamblingan. Theoretical basis used were functional theory and theory of symbols, while the methods used were library research, observation, and interviews. The data were analyzed qualitatively. From the data analysis, it is known that the area had been inhabited from prehistoric (Planting Era) continued to Perundagian (megalithic tradition), and then to the Hindu-Buddhist (Classical Period in 9th century), continued to the Dutch Colonial Period. Culture that flourished in Prehistoric Time namely ancestor and nature power worship to invoke fertility, safety, by using the media of stone throne, menhir (upright stone), and dolmen (stone table), which until now still utilized and conserved. During the Hindu Buddhist Period, ancestor worship continued by using media in the forms of goddess statue, the worship of the gods Trimurti, the existance of social stratification, and developing metal crafts. In the Dutch colonial era, there were cultural influences in architecture, which combined with the local architecture and up to now are still preserved and turned into a tourist attraction.Penelitian peradaban kawasan situs Tamblingan adalah bagian dari penelitian Kawasan Tamblingan Untuk Pengembangan Destinasi Wisata yang dilakukan oleh Balai Arkleologi Denpasar tahun 2012. Penelitian Peradaban Kawasan Tamblingan yaitu: ingin mengetahui sejarah hunian dan kehidupan sosial budaya yang berkembang di kawasan Tamblingan. Landasan teori yang digunakan adalah teori fungsional, dan simbol, sedangkan metode yang digunakan yaitu: perpustakaan, observasi, dan wawancara. Analisis data yang digunakan adalah analisis kualitatif. Dari analisis data yang dilakukan bahwa kawasan situs Tamblingan telah dihuni dari masa prasejarah (bercocok tanam) berlanjut ke masa perundagian (tradisi megalitik), kemudian ke masa Hindu- Buddha (klasik abad IX M), terus ke masa kolonial Belanda. Budaya yang berkembang pada masa prasejarah pemujaan terhadap nenek moyang dan kekuatan alam untuk memohon kesuburan, keselamatan, dengan media pemujaan tahta batu, menhir, dan dolmen, sampai saat sekarang masih dimanfaatkan dan dilestarikan. Pada masa Hindu Budha pemujaan terhadap leluhur berlanjut dengan media pemujaan arca perwujudan Bhatara-Bhatari, pemujaan terhadap dewa Trimurti, sudah ada pelapisan sosial, berkembang kerajinan logam. Pada masa kolonial Belanda, terdapat pengaruh budaya bidang arsitektur yang dipadukan dengan arsitektur lokal dan sampai saat sekarang masih dilestarikan dan dijadikan obyek wisata